Diversity and Relative Abundance of Insect Pollinators on Pigeon Pea (Cajanus cajan L.) in Gajapati District of Odisha - Padhy, Deepayan; Satapathy, Chitta Ranjan; Borkataki, Shimantini; Shankar, Tanmoy; Ray, Soumik (Legume research, 2024)
Background: Many cross pollinated flowering plants rely on pollinators for reproduction and survival. The pigeon pea (arhar), Cajanus cajan L., is the India’s most important pulse crop. It attracts pollinators because to its cross pollination nature, possible nectar and pollen source, attractive colour and scent of the seeds and timing of blossoming. As a result, a complete research of pigeon pea insect pollinator fauna shall be used to conserve those fauna for increasing pigeon pea pollination effectiveness. Methods: Diversity of different pollinating agents associated with the crop pigeon pea by observing their abundance, diversity, percentage contribution, dominance status and diversity following the statistical diversity indexes were recorded during Kharif, 2021-22 in the state of Odisha where the insect pollinators’ fauna was recorded through fixed plot survey. Result: Megachille lanata (Fabricius) was found to be the most dominant pollinator throughout the flowering period among seven different pollinators of order Hymenoptera. M. lanata and Megachille disjuncta (Fabricius) shown higher foraging activity i.e. 6.02 bees/5 min/m2 and 4.25 bees/5 min/m2 respectively. Subdominant class represented maximum species among different dominant status classes exhibited. Very less diversity was observed throughout the season but still more diversity has been observed at mid flowering stags during 10:00-11:00 AM..